2018
DOI: 10.3389/fmars.2018.00370
|View full text |Cite
|
Sign up to set email alerts
|

Bolidophyceae, a Sister Picoplanktonic Group of Diatoms – A Review

Abstract: Pico-and nano-phytoplankton (respectively, 0.2-2 and 2-20 µm in cell size) play a key role in many marine ecosystems. In this size range, Bolidophyceae is a group of eukaryotes that contains species with cells surrounded by 5 or 8 silica plates (Parmales) as well as naked flagellated species (formerly Bolidomonadales). Bolidophyceae share a common ancestor with diatoms, one of the most successful groups of phytoplankton. This review summarizes the current information on taxonomy, phylogeny, ecology, and physio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
36
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1
1

Relationship

4
6

Authors

Journals

citations
Cited by 32 publications
(49 citation statements)
references
References 105 publications
(132 reference statements)
13
36
0
Order By: Relevance
“…Among Dictyochophyceae, the main ASV matches with 97.7% similarity Helicopedinella tricostata and with higher similarity (99.2%) an undescribed strain (RCC2289) isolated from the Arctic (Balzano et al 2012a), suggesting that this ASV may correspond to a new species or even genus, while some of the other ASVs match the species Florenciella parvula and Pseudochattonella farcimen. Bolidophyceae were represented by Triparma laevis as well as environmental clades (Kuwata et al 2018). One uncultivated group MOCH-2 (Marine OCHrophyta, Massana et al 2014) was found in many filtered and sorted samples although at low abundance.…”
Section: /58mentioning
confidence: 99%
“…Among Dictyochophyceae, the main ASV matches with 97.7% similarity Helicopedinella tricostata and with higher similarity (99.2%) an undescribed strain (RCC2289) isolated from the Arctic (Balzano et al 2012a), suggesting that this ASV may correspond to a new species or even genus, while some of the other ASVs match the species Florenciella parvula and Pseudochattonella farcimen. Bolidophyceae were represented by Triparma laevis as well as environmental clades (Kuwata et al 2018). One uncultivated group MOCH-2 (Marine OCHrophyta, Massana et al 2014) was found in many filtered and sorted samples although at low abundance.…”
Section: /58mentioning
confidence: 99%
“…The OSD metabarcoding dataset is invaluable to determine the distribution of many phytoplankton groups in coastal waters 9,11,57 . However it must be always emphasized that metabarcoding is not a quantitative method because of biases in the PCR reaction and of the variation in the number of 18S rRNA gene copies per organism 58 However in the case of Mamiellophyceae, because their size is small, the number of copies is low 58 and does not vary too much between the different genera (e.g.…”
Section: Limitations Of the Osd Datasetmentioning
confidence: 99%
“…The phylogenetic analysis recovered that the White Sea bolidophytes refer to three environmental clades (env. clades I, II and III [88] (Figure 4)), in addition to the group corresponding to the genus Triparma. Bolidophyte T. strigata has a worldwide distribution in plankton and is most abundant in polar waters [89][90][91].…”
Section: Discussionmentioning
confidence: 99%